Multi-criteria sustainability analysis of thermal power plant Kolubara-A Unit 2. (15th April 2017) - Škobalj, P.; Kijevčanin, M.; Afgan, N.; Jovanović, M.; Turanjanin, V.; Vučićević, B.
Abstract: The paper presents a possible approach for creating business decisions based on multi-criteria analysis. Seven options for a possible revitalization of the thermal power plant "Kolubara"-A Unit No. 2 with energy indicators of sustainable development (EISD) are presented in this paper. The chosen EISD numerically express the essential features of the analyzed options, while the sustainability criteria indicate the option quality within the limits of these indicators. In this paper, the criteria for assessing the sustainability options are defined based on several aspects: economic, social, environmental and technological. In the process of assessing the sustainability of the considered options the Analysis and Synthesis of Parameters under Information Deficiency (ASPID) method was used. In this paper, the EISD show that production and energy consumption are closely linked to economic, environmental and other indicators, such as economic and technological development of local communities with employment being one of the most important social parameter. Multi-criteria analysis for the case study of the TPP "Kolubara"-A clearly indicated recommendations to decision makers on the choice of the best available options in dependence on the energy policy. Highlights: Options for sustainable generation of electricity have been proposed. Energy Indicators of Sustainable Development have been formed. ASPID methodology has been implemented.